2014
DOI: 10.1038/bjc.2014.478
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with survival in a large series of patients with malignant pleural mesothelioma in New South Wales

Abstract: Background:Although the prognosis of most patients presenting with malignant pleural mesothelioma (MPM) is poor, a small proportion survives long term. We investigated factors associated with survival in a large patient series.Methods:All patients registered with the NSW Dust Diseases Board (2002–2009) were included in an analysis of prognostic factors using Kaplan–Meier and Cox regression analysis. On the basis of these analyses, we developed a risk score (Prognostic Index (PI)).Results:We identified 910 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
74
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 44 publications
11
74
1
Order By: Relevance
“…18,22,23 Linton et al (2014) showed that people with non-epithelioid subtype had a two-fold greater mortality risk than people with epithelioid disease, a hazard rate ratio of 2.0 (95%CI 1.62, 2.48).…”
Section: © 2015 Public Health Association Of Australiamentioning
confidence: 99%
See 2 more Smart Citations
“…18,22,23 Linton et al (2014) showed that people with non-epithelioid subtype had a two-fold greater mortality risk than people with epithelioid disease, a hazard rate ratio of 2.0 (95%CI 1.62, 2.48).…”
Section: © 2015 Public Health Association Of Australiamentioning
confidence: 99%
“…[16][17][18] These studies may be subject to selection bias due to the fact that these data exclude people with non-occupational asbestos exposures, possibly excluding up to 30% of all MPM cases diagnosed during the relevant calendar period in NSW. 18 The aim of this study was to assess malignant mesothelioma incidence, mortality and survival by tumour location and histological subtype using more up-to-date cancer registration data, and to compare differences in 5-year relative survival by subgroup. We hypothesised that the incidence of malignant mesothelioma had increased over time, with variation by tumour location.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These patients should be considered for systemic therapy. Even with treatment, MPM has a poor prognosis with median survival of approximately one-year and cure is very rare (33)(34)(35). The limited efficacy of therapy for MPM highlights the need to develop more effective therapies for MPM which is challenged by the heterogeneity of MPM (with three pathological subtypes), the relatively low incidence of the disease, and the degree of difficulty with assessment of response.…”
Section: Introductionmentioning
confidence: 99%
“…Calretinin is considered the most sensitive and specific positive mesothelioma marker, above all for epithelioid mesothelioma subtype (65). Also the prognostic role of calretinin has been explored: in several studies higher calretinin expression was observed in tumours with more favourable prognosis (58)(59)(60)(61). Lately the correlation of increased calretinin expression with a better survival has been confirmed and its higher expression has been also associated with epithelioid histology subtype (62).…”
Section: Clinical Implications Of Overexpressed Genes In Mpmmentioning
confidence: 99%